2023
DOI: 10.3390/su15031744
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Optimization of Spiral Fertilizer Applicator Based on Artificial Neural Network

Abstract: To determine the optimal fertilizer discharging performance, a spiral fertilizer applicator was designed according to orchard agricultural requirements. The influence of different parameter combinations of the spiral speed, blade diameter, and pitch on the coefficient of variation (CV) of the fertilizer discharge uniformity was predicted using a neural-network-based model by using the Box–Behnken design (BBD) test. According to the extracted results, the neural network model has a good prediction ability, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The working principle of spiral fertilizer dischargers is as follows: the spiral blades rotate around the axis, and under the pushing of the blades, the fertilizer in the fertilizer box is transported to the fertilizer discharge port and discharged. Its structure is shown in Figure 1 [7]. This fertilizer discharger has low requirements for the physical properties of fertilizers and can be flexibly used for the application of granular fertilizers and powdered fertilizers [8].…”
Section: Research Status Of Spiral Fertilizer Dischargersmentioning
confidence: 99%
“…The working principle of spiral fertilizer dischargers is as follows: the spiral blades rotate around the axis, and under the pushing of the blades, the fertilizer in the fertilizer box is transported to the fertilizer discharge port and discharged. Its structure is shown in Figure 1 [7]. This fertilizer discharger has low requirements for the physical properties of fertilizers and can be flexibly used for the application of granular fertilizers and powdered fertilizers [8].…”
Section: Research Status Of Spiral Fertilizer Dischargersmentioning
confidence: 99%
“…When the rotational speed reaches a certain limit, the centrifugal force acting on the fertilizer particles will be large, causing them to be ejected outward, which hinders the proper functioning of the fertilizer applicator. Therefore, it is necessary to limit the rotational speed of the discharge blade [22]. By using the empirical Formula ( 7), the maximum rotational speed is determined to be 100.26 r/min.…”
Section: Design Of Structural Parameters Of Fertilizer Applicatormentioning
confidence: 99%
“…Moreover, they exhibit robustness to minor perturbations, adapting seamlessly to input variations and noise [18]. Currently, artificial neural network models are mainly used for the optimization of food and bioprocess parameters and have not been widely used in the optimization of structural parameters [19,20], but there are a few studies on the prediction of fertilizer discharge performance of fertilizer applicator [21,22]. Bu et al [23] used EDEM simulation software to investigate how the rotational velocity and aperture degree of the fertilizer discharge wheel affect fertilizer application performance.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial neural network (ANN) is a technology used in the field of Artificial Intelligence that represents an interconnected network consisting of multi-layered nodes (neurons), including input and output nodes and weighted connections that are meant to simulate a biological neural network [ 18 , 19 ]. Through years of experiments and research, ANN techniques have demonstrated robust learning capabilities and high prediction accuracy through its ability to identify complex mathematical relationships between input and output variables [ 20 ]. Accordingly, ANN models have been widely used in the literature as predictive techniques in a range of different fields, including healthcare [ 21 , 22 ], sustainable development [ 18 , 19 , 23 ], agriculture [ 23 , 24 ], and material science [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%